Social Action of Creative Economy Actors in the Culinary Sector of Tourism Destination Areas in Padang City - Lubis, Gebi Cahyani Cahyani; Irwan, Irwan; Zusmelia, Zusmelia (Universitas Tanjungpura, 2025)
The focus of the study in this research is to analyze the social actions of creative economic actors in the culinary sector of the tourist destination area of Padang city. the theory used in this theory is the theory of social action put forward by Max Weber. This research uses a qualitative approach with the data analysis process using the thoughts of Miles and Huberman. Data collection techniques were carried out in several ways, namely: document studies, interviews and observations. The results of this study are that creative economic actors in the culinary sector take various kinds of actions in order to maintain culinary products. The actions taken by creative economic actors are to make the product known and can be felt by all circles. That way to create these things there are various forms of social action carried out by creative economic actors in the culinary sub-sector, namely: 1) utilizing the network built by creative economic actors, the network includes networks in social media, family, joint activities and friendships, 2) determining prices in accordance with consumers, 3) making cash payments when taking raw materials, 4) maintaining social and divine values, and 5) maintaining local traditions in creative economic development.The novelty of this research is social action based on social networks and local wisdom